Captain marvel: dark tempest (2023) ebook - Nocenti, Ann (Captain Marvel: Dark Tempest (2023),, 2024)
Collects Captain Marvel: Dark Tempest (2023) #1-5. A new start for Captain Marvel! After facing off against the Brood with the X-Men and losing someone she holds dear, Carol Danvers needs a break. But she's not about to get it now! A slinky new cosmic threat has come for Earth's Mightiest, and they know just which surprise legacy villain to recruit to really wreck Carol's world! When the disgruntled Nitro transports Captain Marvel, Chewie the Flerken, baby Gerry and some cantankerous Luddite troublemakers to a strange planet, Spider-Woman - Gerry's mom - is left in a panic. As the mismatched group figures out how to get along and survive, Jessica Drew desperately seeks out help from some of Earth's greatest heroes! But the deadly menaces keep coming, including the spooky alien Nada and the Feral Five!